A Melopoética do sertão do Moxotó : uma análise da poesia oral do Cordel do Fogo Encantado - Almeida, Adriana Soares de (2013)
This dissertation aims to investigate the relations between music and literature in songs that make the work of the pernambucano group Cordel do Fogo Encantado in order to understand the meanings of these interartistics compositions and how they reinvent the crystallized traditions about the image of the Brazilian backland. Therefore, we chose a corpus consisting of seven songs by Cordel do Fogo Encantado (Profecia, Profecia Final, Chover, A Matadeira, Pedra e Bala,Vou saquear a tua feira e Morte e Vida Stanley), chosen not only for their intersection between literature and music, since the whole work of this group has such intersection, but for their expression of the Brazilian backland, the place of origin of the group. Several implications of this approach appeared and to answer them we followed the pioneering work of Steven Paul Scher, who under the name Melopoetic (melos = singing + poetic) includes studies of musical-literary comparativism, seeking connections between the arts. Along the ideas of this author, the notion of Cultural Melopoetic present in the works of Solange Ribeiro de Oliveira, also served as basis. Furthermore, we consider appropriate the dialogue between melopoetic and the concept of oral poetry developed by medievalist Paul Zumthor, comprising the study of orality not only in literature, but in different manifestations in which the voice is the driving force, as well as his idea of performance coupled with the work of Ruth Finnegan under the same topic. The work of Cordel do Fogo Encantado, uniting the afro indigenous music in the backland of Moxotó to the sound of violas and rhythms of popular folklore was increased of literature to portray the backland where tradition and modernity are intertwined, creating a peculiar work. The analytical process sought to demonstrate how the presence of literature and music manifests itself in the songs worked and how this connection is responsible for transcreate a hybrid backland that insists on reinventing itself